A Photocontrolled Molecular Rotor Based on Azobenzene-Strapped Mixed (Phthalocyaninato)(Porphyrinato) Rare Earth Triple-Decker - Wenxin Lu; Tiantian Mu; Yuehong Zhang; Bo Chen; Huantao Guo; Luyang Zhao; Peng Wang; Yongzhong Bian (Molecules)
Effectively regulating the rotary motions of molecular rotors through external stimuli poses a tremendous challenge. Herein, a new type of molecular rotor based on azobenzene-strapped mixed (phthalocyaninato)(porphyrinato) rare earth triple-decker complex Azo-1 is reported. Electronic absorption and 1H NMR spectra manifested the reversible isomerization of the rotor Azo-1 between the trans configuration and the cis configuration. The rotational behavior of phthalocyanine rotator in two configurations were investigated by VT-1H NMR experiments, and the results indicated that the phthalocyanine rotator possessed a smaller rotational energy barrier in the cis isomer than in the trans isomer, which was also supported by DFT calculations. This result demonstrates that the rotation of phthalocyanine rotator in (phthalocyaninato)(porphyrinato) rare earth triple-decker complex can be successfully modulated by photo-isomerization via altering irradiation.